Rachunek kosztów docelowych i możliwości jego wykorzystania w szpitalach - Kludacz, Magdalena (Target Costing and Its Application to Hospitals, 2008)
There have been many changes in the domestic market of medical services since 1999. They affect the growing competition among hospitals. The cost management skills play a very important role in such conditions. They require continuous monitoring, analyzing and controlling medical services costs in order to rationalize them. One of the main tools of cost management is target costing. This article presents the reasons for the development, the structure, principles, and factors determining the application of target costing to hospitals.
Prace Naukowe Uniw, s. 131-141ersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 36, s. 131-141